2009
DOI: 10.1017/s0924270800032841
|View full text |Cite
|
Sign up to set email alerts
|

3 Review of multiple sclerosis at the neurology clinic in Sarajevo during 2006

Abstract: Introduction/Objectives: An important contribution of B cells and autoantibodies has been demonstrated in the pathogenesis of multiple sclerosis (MS) leading to interest in the use of such autoantibodies as diagnostic or prognostic markers. A common problem in studies of humoral immunity is that accurate detection of antibodies depends highly on the conformation of the antigens used for detection. Therefore widely used techniques, including ELISA and Western blotting, may fail to detect reactivity against epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Finally, 128 studies were included in the qualitative and quantitative synthesis (Supplementary Table 2). 12…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 128 studies were included in the qualitative and quantitative synthesis (Supplementary Table 2). 12…”
Section: Resultsmentioning
confidence: 99%
“…5 It is confirmed that atherosclerosis with higher intraocular pressure has a bad influence on pulse volume level in glaucoma. 6 So, we have done this study to evaluate the fasting lipid profile level in normotensive and non-diabetic glaucoma patients coming to our hospital in OPD of Ophthalmology department G.G.S. Medical College, Faridkot.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS) characterized by the deterioration of myelin and axons in various parts of the brain and spinal cord (1, 2). It more often affects women than men (ratio from 3:1 to 1.8:1).…”
Section: Introductionmentioning
confidence: 99%